(D
3 − 3DD
′2 − 2D
′3
)z = cos(x + 2y)
(D3-3DD'-2D'3)z=Cos(x+2y)
"\\because" D=m and D'=1
The auxiliary equation is;
m3-3m-2=0
(m+1)(m+1)(m-2)=0
m=-1,-1,2
Therefore C.F=f1(y-x)+xf2(y-x)+f3(y+2x)
Now,
P.I="\\frac{1}{D^{3}-3DD'^{2}-2D'^{3}}Cos(x+2y)"
But D2=-1,D'2=-22=-4
P.I="\\frac{1}{(-1)D-3D(-4)-2(-4)D'}Cos(x+2y)"
="\\frac{1}{-D+12D+8D'}Cos(x+2y)"
= "\\frac{1}{11D+8D'}Cos(x+2y)"
="\\frac{D}{11D^{2}+2DD'}Cos(x+2y)"
="\\frac{D}{11(-1)+8(-2)}Cos(x+2y)\\ \\because D^{2}=-1^{2}\\ and\\ D-D'=-1*2=-2"
P.I="\\frac{D}{-11-16}\\int Cos(x+2y)"
="\\frac{-1}{27}[-Sin(x+2y)]"
="\\frac{1}{27}Sin(x+2y)"
The general solution becomes;
y=C.F+P.I
=f1(y-x)+xf2(y-x)+f3(y+2x)+"\\frac{1}{27}Sin(x+2y)"
Comments
Leave a comment